Removal of Oil Content from Oil-Water Emulsions Using Iron Oxide/Bentonite Nano Adsorbents. (December 2020) - Ewis, Dina; Benamor, Abdelbaki; Ba-Abbad, Muneer M.; Nasser, Mustafa; El-Naas, Muftah; Qiblawey, Hazim
Graphical abstract: Abstract: Water scarcity is a challenge that is faced worldwide to secure sustainable good quality water resources. Produced water, associated with the production of gas and oil, usually comes as oil contaminated water, creating real problems in water resources' management. Removing oil content from produced water is crucial to meet the discharge limits set by governmental legislation. Nanocomposites have attracted attention as potential adsorbents due to their high ability to remove oil content from produced water. In this work, Iron oxide/Bentonite nanocomposites (Fe3 O4 /Bent NC) were synthesized using ultrasound-assisted co-precipitation methods and evaluated them for oil removal from emulsified oil solutions. SEM, EDS, TEM, XRD, FTIR and VSM were used to characterize the synthesized nanocomposites, confirming the successful formation of superparamagnetic Fe3 O4 /Bent NC. In addition, the characterization analysis showed that iron oxide nanoparticles were uniformly distributed over bentonite surface with a particle size of 13.55 nm. Performance analysis of oil removal using synthesized Fe3 O4 /Bent NC was carried out by assessing the effect of Nano-adsorbent dosage, oil initial concentration, adsorption time, and solution pH using batch experiments. A removal percentage of 67% after 90 minutes using only 0.1 grams at 100 ppm oil concentration was obtained. The experimental data were described by Langmuir isotherm model, which suggests a monolayer adsorption of oil onto synthesized Fe3 O4 /Bent NC. The kinetics data were best described using pseudo-second-order kinetics model. Overall, this study confirms the applicability of Fe3 O4 /Bent NC as a feasible adsorbent for oil removal from produced water.